Bob Marley and the Wailers [videorecording (DVD)] : catch a fire - Marley, Bob; Marre, Jeremy; Wailer, Bunny; Tosh, Peter; Barrett, Aston; Shakespeare, Robbie; Marley, Rita; Blackwell, Chris, 1937- (Eagle Vision, 1999)
Explores the making and release of Bob Marley and the Wailers' 1973 album.